Accident investigation techniques : best practices for examining workplace incidents - Oakley, Jeffrey S.; Sturm, Peter (Industrial safety consultant) (American Society of Safety Professionals, 2022)
"Peter Sturm and Jeffrey Oakley provide a concise comparison of accident/incident investigation techniques that can be used to help companies and safety professionals analyze accidents and feel assured that the causes have been properly determined and that corrective actions will prevent reoccurrence. This third edition updates the second edition and covers all aspects of accident investigation from theory to organizing, gathering and analyzing data, to reporting, recommendations, and follow-up. This edition integrates the new research, updates the relevant references, and introduces changes that have occurred and continue to occur as workplace safety and investigations evolve and improve. The authors also reference the only consensus standard focusing on investigating incidents, CSA Z1005:21, Workplace Incident Investigation"-- Provided by publisher.
Jeffrey S. Oakley appeared as the first named author on all earlier editions.
Keywords: Industrial accidents -- Investigation.; Accident investigation.; elektronické knihy; electronic books